Redox proteomic evaluation of bleaching and alkali damage in human hair. (22nd July 2013) - Dyer, J. M.; Bell, F.; Koehn, H.; Vernon, J. A.; Cornellison, C. D.; Clerens, S.; Harland, D. P.
Synopsis: Objective: Protein modification and damage in human hair, resulting from environmental, cosmetic and grooming stresses, create changes to visual and tactile characteristics and correlates with consumer perception of quality. This study outlines molecular‐level evaluation of modification resulting from peroxide (bleaching) and alkaline straightening (relaxing) treatments. Methods: Redox proteomic profiling of virgin, bleached and relaxed hair tresses was performed, with comprehensive qualitative characterization of modification and semi‐quantitative evaluation of damage through adaptation of a new damage scoring system. Modifications were mapped to specific locations in the hair proteome and a range of potential damage marker peptides identified. Results: Virgin hair contained a baseline level of modification, consistent with environmental oxidative insult during hair growth. Hydrogen peroxide bleaching resulted in significantly increased levels of oxidative damage observable at the molecular level. This treatment also resulted in enhanced levels of dehydroalanine and dehydration products; modifications typically associated with alkali or thermal treatment and not previously been reported as a product of hair bleaching. Relaxation treatment with sodium hydroxide increased the formation of dehydroalanine and dehydration products and moderately enhanced the levels of oxidation. Cysteine was the predominant modification site for both bleaching and alkali damage. Conclusion: This study validates the utility and power of redox proteomic–based approaches to characterizing hair modification. This offers potential application to a wide range of damage types, as well as evaluation of new damage mitigation and repair technologies. Abstract : Protein modification and damage in human hair, resulting from environmental, cosmetic and grooming stresses, creates changes to visual and tactile characteristics and correlates to consumer perception of quality. This study outlines molecular‐level evaluation of modification resulting from peroxide (bleaching) and alkaline straightening (relaxing) treatments. Hydrogen peroxide bleaching resulted in significantly increased levels of oxidative damage observable at the molecular level. This treatment also resulted in enhanced levels of dehydroalanine and dehydration products; modifications typically associated with alkali or thermal treatment and not previously been reported as a product of hair bleaching.